WOMEN’S ROLE IN DEVELOPMENT SOCIAL ECONOMY IN THAI NGUYEN PROVINCE - Hoàng Thị Mỹ, Hạnh; Lê Thị, Anh (SCIENTIFIC JOURNAL OF TAN TRAO UNIVERSITY, 2023)
Throughout the nation’s history, Vietnamese women in general and Thai Nguyen women in particular have made great contributions to the cause of the national liberation struggle and national construction. In wartime, women are brave soldiers, in peacetime, they are laboring heroes working together to build a richer and more beautiful country. Especially, in the current trend of integration and development, women continue to promote and affirm their great role in socio-economic development. Women have participated in all fields of economy, politics, culture, society, security and defense..., affirming their role in family and society. The article researches the role of women in Thai Nguyen province in the economic development of Thai Nguyen province. This is a period in the renewal period in which the Thai Nguyen women’s movement has made new breakthroughs. And achieved many important achievements, contributing to the economic development of the province, thereby affirming the position and role of women in Thai Nguyen province in the period of accelerating industrialization - modernity. nationalization and international integration.